Asymptotic Bethe ansatz of ABJM open spin chain from giant graviton - Hui-Huang Chen (Journal of High Energy Physics, 2019)
Abstract In our previous work, the two-loop integrability of ABJM determinant like operator has been well established. In this paper, we push the integrability to all loop orders. The asymptotic Bethe ansatz equations for ABJM determinant like operator (open string attached on giant graviton) are obtained. In the derivation, the symmetries preserved by the bulk and the boundary played a crucial role. Taking the weak coupling limit and applying appropriate fermionic dualities, we obtained a different set of scalar sector Bethe equations with our previous results. When the “gauge” transformation on Bethe equations was introduced, the discrepancy disappeared.